PENGARUH KEPEMIMPINAN, MOTIVASI KERJA DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MEDIASI PADA KPP PRATAMA PALEMBANG ILIR TIMUR - Perdana, Rory Galih; Edizal, Edizal; Sakarina, Sari (LPPM Universitas Multi Data Palembang, 2024)
Abstract: This research aims to determine and prove the influence of leadership, work motivation and work motivation on employee performance with job satisfaction as a mediating variable at Kpp Pratama Palembang Ilir Timur, both directly and indirectly. The population in this study were KPP Pratama Palembang Ilir Timur employees, totaling 110 people. This study used simple random sampling, with the Slovin formula with a sample size calculation based on an error of 5%. so the number of samples used was 86 research samples. Data analysis uses the Structural Equation Model (SEM) analysis method which is operated through the Partial Least Square (PLS) program. The results of this research show that, Leadership influences Job Satisfaction, Job Motivation influences Job Satisfaction, Job Motivation influences Job Satisfaction, Leadership influences Performance, Work Motivation influences Performance, Work Motivation influences Performance, Job Satisfaction influences Performance, Leadership influences Performance through Job Satisfaction, Work Motivation influences Performance through Job Satisfaction, Work Motivation influences Performance through Job Satisfaction. The R2 value for the latent variable Job Satisfaction as a mediating variable is 0.967, which means that this value identifies that variations in Employee Job Satisfaction can be explained by exogenous latent variables (Leadership, Work Motivation and Work Motivation) amounting to 96.7% while the remaining 3.3% explained by other variables. The R2 value for the latent variable Performance is 0.987, which means that this value identifies that variations in performance can be explained by exogenous variables (Leadership, Work Motivation, Work Motivation and Job Satisfaction) amounting to 98.7% while the remaining 1.3% is explained by variables that are not. contained in the research.